INVESTIGATING MUSLIM STUDENT’S AWARENESS TOWARDS HALAL LABELLED COSMETICS (STUDY IN BANDUNG) - Anggraeni, Vika; Hudrasyah, Herry (Journal of Business and Management, 2017)
Abstract. For Muslim consumers, consuming halal products is one of the obligations based on religious Shari'a. Halal products are consumed or used in any variety, including cosmetics product. Nowadays, cosmetics and personal care products are a fundamental part of daily lives. However, according to previous studies the female consumers do not completely aware to the halalness of their cosmetics product. Thus, because of the growing and demand of halal cosmetics product, it is important to figure out the halal cosmetics awareness among young generation. Findings on halal cosmetics in Indonesia is straitened. Furthermore, the purpose of this study is to describe the female Muslim student’s awareness towards halal labeled cosmetics, specifically, in Bandung city. To know the students’ awareness towards halal label cosmetics, researcher author combining several concept of customer awareness for measuring consumer awareness since there is no exact variables in measuring the awareness. The variables are consists of a socio-demographic profiles, media advertisement, and product knowledge. By using Qualitative Research method with semi-structured interview to the seven participants, researchers can understand the phenomenon about halal awareness among Muslim students. This study also used triangulation by interviewing some expert in cosmetics industry. The result found that students had awareness towards the halal labeled cosmetics. In conclusion, the participants who had attended Islamic religious school has more understanding about religious education and more aware towards halal cosmetics. They had aware towards the information about halal cosmetics in the advertisement. The participants also have their awareness towards their knowledge through cosmetics product, including ingredients, logo and halal certification. Based on this study, there is another factor that can influence the consumer awareness towards halal labeled cosmetics. It includes the halal regulation and cosmetics industry. Furthermore, this study expects to give some recommendations and better understanding the importance of knowledge of a halal cosmetic product and shows how the industry and government can better accommodate these needs. Keywords: Consumer Awareness, Halal Labelled Cosmetics, Halal Product Consumption